Preparation method of water-based fluorocarbon coating containing micro-nano fold structure

By introducing modified alumina filler into the aqueous fluorocarbon coating and forming a micro- or nano-scale fold structure, the shortcomings of aqueous fluorocarbon coatings in water-based fluorocarbon coatings in terms of water-based fluorocarbon coatings are solved, and the coating performance is achieved. Significant improvement.

CN119432173APending Publication Date: 2025-02-14YEJIAN NEW MATERIAL +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411539780.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing water-based fluorocarbon coatings are weaker in terms of water resistance, corrosion resistance and weather resistance than solvent-based fluorocarbon coatings, and are difficult to meet certain high-demand application scenarios.

Method used

By introducing modified alumina filler into aqueous fluorocarbon coatings and using isopropyl distearyloxy aluminate as coupling agent, a micron or nano-scale fold structure is formed to improve the density and resistance of the coating. Corrosion performance.

Benefits of technology

It has achieved improved water resistance, corrosion resistance and weather resistance of water-based fluorocarbon coatings, extended service cycle, and improved the pollution resistance and corrosion resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432173A_ABST
    Figure CN119432173A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a water-based fluorocarbon coating with a micron-sized fold structure. In order to form micron-sized layered wrinkles, the coating takes isopropyl distearoyloxy aluminate as a coupling agent and modified aluminum oxide powder as a filler, and better dispersion performance of the modified filler in a water-based fluorocarbon emulsion is realized through process regulation and control. Compared with a traditional water-based fluorocarbon coating, the water-based fluorocarbon coating is good in dispersing performance, has a layered wrinkle structure, is low in porosity and slow in increase, delays invasion of a corrosive medium, reduces the corrosion speed, prolongs the failure time and has long-acting performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of a coupled modified aluminum oxide filler and a long-acting water-based fluorocarbon composite coating, and in particular to a method for preparing a water-based fluorocarbon coating containing a micro-nano-scale wrinkle structure. Background Art

[0002] In view of the problem that steel widely used in my country is prone to rust and corrosion failure, an effective way to improve its corrosion resistance is to apply a protective coating on its surface. Among the environmentally friendly water-based coatings that are both transparent, weather-resistant and corrosion-resistant, the more unique water-based fluorocarbon coating has great economic value and relatively good protective performance. This coating can effectively prevent the damage of ultraviolet rays, isolate the metal surface from the contact with the external environment, form a protective barrier, and slow down the corrosion process. Water-based fluorocarbon coating is a special type of coating. Its unique chemical structure gives it excellent anti-fouling, weather-resistant, and chemical corrosion resistance. Compared with traditional organic solvent-based fluorocarbon coatings, water-based fluorocarbon coatings use water as a solvent, have lower volatile organic compound (VOC) emissions, are more environmentally friendly, and are suitable for various application scenarios. Fluoropolymer is one of the main components of water-based fluorocarbon coatings. It is usually polymerized by fluorocarbon hydrocarbon monomers to form a polymer chain structure. In this structure, fluorine atoms replace part or all of the hydrogen atoms to form fluorine-containing CF bonds. This CF bond gives the water-based fluorocarbon coating with this fluoropolymer as the main film-forming substance strong stability. For example, the two-component water-based fluorocarbon coating mentioned in CN117363184A is composed of aliphatic polyisocyanate, cosolvent, FEVE water-based fluorocarbon resin, additives, pigments and deionized water, which improves the weather resistance and durability of the water-based fluorocarbon coating to meet the anti-corrosion needs of bridges, marine buildings, power facilities, ships, chemical equipment and other fields.

[0003] Since water-based fluorocarbon coatings still inevitably have weaker water resistance, corrosion resistance and weather resistance than solvent-based fluorocarbon coatings. Therefore, it is possible to consider introducing inorganic particles into the coating to fill the gaps in the coating, increase the coating density, and improve its mechanical properties and corrosion resistance. In order to improve the performance of inorganic powder particles in the coating, a coupling agent can be added to the coating system to improve the dispersion performance. Among them, silane series coupling agents are widely used in various inorganic powder modifications and are relatively mature. For example, the modified phosphorus-containing Si-171 or KH-550 coupling agents mentioned in WO2021238146A1, phosphorus-containing flame retardants and nano flame retardants have a synergistic effect in flame retardant effects, which can improve the flame retardant properties of composite flame retardants, so that the flame retardant properties of high-impact polystyrene composite materials are enhanced. As a less used coupling agent, aluminate coupling agents have been less studied in powder surface modification and are mainly based on mechanical properties. For example, CN117264431A mentions the use of aluminate coupling agent to modify magnesium hydroxide and dope it into asphalt for modification, thereby reducing the release of asphalt smoke.

[0004] High-performance coatings are completely dependent on surface integrity, morphology, microstructure, stress state, interface structure, cohesion and adhesion, in which the structure of the coating plays a very important role. Coatings containing micron- or nano-scale structures are always manufactured by various techniques to meet the requirements of unique performance under special working conditions. For example, an aerogel thermal insulation nano coating described in CN115011153A uses aerogel fillers in the prepared coating to prepare a nano thermal insulation coating doped with a three-dimensional grid structure. The modification of graphene described in CN111410911A is to graft special oxygen-containing functional groups on the graphene group. The oxygen-containing functional groups can accelerate the high-density cross-linking reaction of special epoxy and special curing agent to obtain a high-density cured coating film, thereby improving the dispersibility and physical and mechanical properties of graphene in the coating film. It is reported that the wrinkled structure in the coating has special properties. For example, CN113062116A mentions a bionic structure strain-insensitive conductive fiber and its preparation method. When the elastic fiber surface has a layer of elastic polymer wrinkles, it has excellent insensitive performance under high tensile strain and alleviates the sensing hysteresis to a certain extent.

[0005] Therefore, the preparation method of inducing the construction of micron- or nano-scale structures by coupling modified inorganic powders and combining them with water-based fluorocarbon coatings has great potential and prospects in improving their water resistance and corrosion resistance. Summary of the invention

[0006] The purpose of the present invention is to improve the shortcomings of the prior art and provide a method for preparing a water-based fluorocarbon coating containing a micro-nano-scale wrinkle structure. The water-based fluorocarbon coating containing a micron-scale wrinkle structure is prepared by modifying nano-Al2O3 with isopropyl distearoyloxyaluminate (GR-AL18). 2 O 3 As filler (DL-Al 2 O 3 ) Add water-based fluorocarbon resin, wetting agent, emulsifier and defoamer, stir, ultrasonically disperse to obtain water-based fluorocarbon emulsion, and then prepare it by coating and curing.

[0007] The technical solution of the present invention is: a method for preparing a water-based fluorocarbon coating with a micro-nanoscale wrinkle structure, and the specific steps are as follows:

[0008] (1) using anhydrous ethanol as a solvent and isopropyl distearoyloxyaluminate as a solute to prepare a modifier with a mass concentration of 1-3%, adding 5-6% of the mass of the modifier to the solution system to form a suspension, stirring at room temperature, reacting for 240-270 minutes, centrifugally washing and drying after stirring to obtain modified nano alumina; (alumina is α-crystalline, with a particle size range of 10nm-500nm);

[0009] (2) Using the modified nano-alumina as filler, adding water-based fluorocarbon resin, wetting agent, emulsifier and defoaming agent, stirring, and ultrasonically dispersing to obtain a water-based fluorocarbon emulsion; coating the emulsion on a substrate (preferably carbon steel), drying in an oven and curing to form a coating.

[0010] Preferably, the stirring in step (2) is performed for 30-50 minutes at a stirring rate of 800-1200 r / min. After the stirring is completed, ultrasonic treatment is performed for 30-50 minutes.

[0011] Preferably, the components and their weight parts in the aqueous fluorocarbon emulsion are: 40-50 parts of aqueous fluorocarbon resin, 1 part of filler, 0.5-2 parts of wetting agent, 1-2 parts of emulsifier, and 1-2 parts of defoamer.

[0012] Preferably, the wetting agent is polyoxyethylene alkylphenyl ether or polyoxyethylene fatty acid ester; the emulsifier is OP-10, polysorbate TW-85 or sodium dodecylbenzene sulfonate (SDBS); and the defoaming agent is 1-octanol, liquid paraffin or silicone.

[0013] Preferably, the thickness of the latex coated on the carbon steel substrate is 150 um ± 10 um; the thickness of the coating after drying and curing is 60 ± 5 um.

[0014] Preferably, the prepared powder is subjected to contact angle measurement, and the coating is subjected to electrochemical measurement, scanning electron microscopy photography and salt spray test to evaluate its performance.

[0015] Beneficial effects: Compared with traditional fluorocarbon coatings, the present invention has the following advantages:

[0016] (1) Water-based fluorocarbon coatings are environmentally friendly, safe and easy to construct, meeting a variety of construction conditions.

[0017] (2) The long carbon chain of isopropyl distearoyloxyaluminate is similar to the skeleton of fluorocarbon resin, and has good compatibility when formulated into an emulsion and cured into a coating.

[0018] (3) The modified alumina doping has good dispersibility. Through a specific process, a special micron-scale structure can be formed in the cured coating to improve the coating's ability to resist the invasion of corrosive media, thereby increasing its service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The water contact angle pictures of Comparative Example 2 and Examples 1-5; wherein a: Comparative Example 2; b: Example 1; c: Example 2; d: Example 3; e: Example 4; f: Example 5;

[0020] Figure 2 These are microscopic images of the emulsions of Comparative Examples 1-2 and Example 1; a: Comparative Example 1; b: Comparative Example 2; c: Example 1;

[0021] Figure 3 The scanning electron microscope and EDS spectra of the coating interface of Comparative Examples 1-2 and Example 1; a: ×3000 Comparative Example 2; b: ×5000 Comparative Example 2; c: ×3000 Example 1; d: ×5000 Example 1; e: EDS data;

[0022] Figure 4 The impedance change diagram of the coating of Comparative Examples 1-2 and Example 1 at different immersion times; a: Comparative Example 1; b: Comparative Example 2; c: Example 1; d: Impedance fitting;

[0023] Figure 5 The graphs of coating porosity changes of Comparative Examples 1-2 and Example 1 at different immersion times;

[0024] Figure 6 The graph is a graph showing the change in coating corrosion area of ​​Comparative Examples 1-2 and Example 1 under different salt spray test times. DETAILED DESCRIPTION

[0025] Comparative Example 1: Prepare water-based fluorocarbon emulsion, 40 parts of water-based fluorocarbon resin, 0.5 parts of wetting agent polyoxyethylene fatty acid ester, 1 part of emulsifier SDBS, and 1 part of defoaming agent silicone. Stir for 35 minutes at a stirring rate of 900r / min. Perform ultrasound after stirring for 35 minutes. Apply on carbon steel and dry. The coating controls the wet film thickness to be 140um and the dry film thickness to be 55um.

[0026] Comparative Example 2: Prepare an ethanol solution with a concentration of 98%, add 5g of nano-alumina powder to form a suspension,

[0027] Stir at room temperature at a rate of 400r / min. After stirring, centrifuge and dry to obtain unmodified nano alumina. Prepare water-based fluorocarbon emulsion, 45 parts of water-based fluorocarbon resin, 0.5 parts of wetting agent polyoxyethylene alkyl phenyl ether, 1 part of emulsifier TW-85, 1 part of defoaming agent liquid paraffin, and 1 part of unmodified nano alumina filler. Stir for 35 minutes at a stirring rate of 900r / min. After stirring, perform ultrasound for 35 minutes. Apply on carbon steel and dry.

[0028] The coating controls the wet film thickness to be 150um and the dry film thickness to be 60um.

[0029] Example 1: Prepare ethanol-GR-AL18 coupling agent solution, a modifier with a concentration of 1%, add 5% nano-alumina powder of the modifier mass to form a suspension, stir at room temperature, the rate is 400r / min, and the reaction time is 240min. After stirring, centrifuge and dry to obtain modified nano-alumina; prepare water-based fluorocarbon emulsion, 50 parts of water-based fluorocarbon resin, 0.5 parts of wetting agent polyoxyethylene fatty acid ester, 1 part of emulsifier OP-10, 1 part of defoamer 1-octanol, and 1 part of modified filler. Stir for 30 minutes at a stirring rate of 800r / min. After stirring, perform ultrasound for 30 minutes. Apply on carbon steel and dry. The coating controls the wet film thickness to be 150um and the dry film thickness to be 60um.

[0030] Example 2: Prepare ethanol-GR-AL18 coupling agent solution, a modifier with a concentration of 1.5%, add 5% nano-alumina powder by mass of the modifier to form a suspension, stir at room temperature, the rate is 450r / min, and the reaction time is 245min. After stirring, centrifuge and dry to obtain modified nano-alumina. Prepare water-based fluorocarbon emulsion, 40 parts of water-based fluorocarbon resin, 1 part of wetting agent polyoxyethylene fatty acid ester, 1 part of emulsifier OP-10, 1 part of defoamer 1-octanol, and 1 part of modified filler. Stir for 30 minutes at a stirring rate of 800r / min. After stirring, perform ultrasound for 30 minutes. Apply on carbon steel and dry. The coating controls the wet film thickness to 160um and the dry film thickness to 65um.

[0031] Example 3: Prepare ethanol-GR-AL18 coupling agent solution, a modifier with a concentration of 2%, add 5.5% of the modifier mass of nano-alumina powder to form a suspension, stir at room temperature, the rate is 500r / min, and the reaction time is 250min. After stirring, centrifuge and dry to obtain modified nano-alumina. Prepare water-based fluorocarbon emulsion, 45 parts of water-based fluorocarbon resin, 1 part of wetting agent polyoxyethylene fatty acid ester, 1.5 parts of emulsifier OP-10, 1.5 parts of defoamer 1-octanol, and 1 part of modified filler. Stir for 35 minutes at a stirring rate of 900r / min. After stirring, perform ultrasound for 35 minutes. Apply on carbon steel and dry. The coating controls the wet film thickness to 160um and the dry film thickness to 65um.

[0032] Example 4: Prepare ethanol-GR-AL18 coupling agent solution, a modifier with a concentration of 2.5%, add 6% nano-alumina powder by mass of the modifier to form a suspension, stir at room temperature, the rate is 550r / min, and the reaction time is 260min. After stirring, centrifuge and dry to obtain modified nano-alumina. Prepare water-based fluorocarbon emulsion, 50 parts of water-based fluorocarbon resin, 1.5 wetting agent polyoxyethylene fatty acid ester, 2 parts of emulsifier OP-10, 2 parts of defoamer 1-octanol, and 1 part of modified filler. Stir for 35 minutes at a stirring rate of 900r / min. After stirring, perform ultrasound for 35 minutes. Apply on carbon steel and dry. The coating controls the wet film thickness to 160um and the dry film thickness to 65um.

[0033] Example 5: Prepare ethanol-GR-AL18 coupling agent solution, a modifier with a concentration of 3%, add 6% nano-alumina powder by mass of the modifier to form a suspension, stir at room temperature, the speed is 600r / min, and the reaction time is 270min. After the stirring is completed, centrifuge and dry to obtain modified nano-alumina. Prepare water-based fluorocarbon emulsion, 50 parts of water-based fluorocarbon resin, 2 parts of wetting agent polyoxyethylene fatty acid ester, 2 parts of emulsifier OP-10, 2 parts of defoaming agent 1-octanol, and 1 part of modified filler. Stir for 35 minutes at a stirring rate of 900r / min. After stirring, perform ultrasound for 35 minutes. Apply on carbon steel and dry. The coating controls the wet film thickness to 160um,

[0034] Dry film thickness 65um.

[0035] Figure 1 The water contact angle pictures of the powders obtained under different preparation conditions of the comparative examples and the examples are measured by tableting. In comparative example 2, the unmodified powder tablets are directly wetted by water, but in examples 1-5, the contact angle reaches a maximum of 149.28°, which has excellent water resistance.

[0036] The emulsions prepared in Comparative Examples 1-2 and Example 1 were photographed under a microscope. Figure 2 . Figure 2 In the field of view of a, emulsion droplets and resin particles can be seen, while Figure 2 A larger Al 2 O 3 Agglomeration, the diameter can reach 60-80um. Figure 2 As can be seen in c, most of the DL-Al 2 O 3 The particles are dispersed more densely in the emulsion, and no large-sized agglomerates appear. The microstructures of the emulsions in Examples 2-5 are similar to those in Example 1, indicating that DL-Al 2 O 3It has good dispersibility in water-based fluorocarbon emulsion.

[0037] The SEM results of the coating cross section are shown in Figure 3 Under the magnification of 3000 times, the preparation conditions of comparative example 2 showed obvious agglomerated particles, and the size of the agglomerated part was about 1.2 μm. Under the preparation conditions of example 1, dense and uniform stripe wrinkles appeared in c and d, and the stripe spacing was 0.6 μm. Figure 3 As shown in e, the aluminum content in the wrinkle area is relatively high, reaching 44.74w%, proving that the wrinkles are formed by DL-Al 2 O 3 Among them, Examples 2-5 all have stripe wrinkles with similar morphology and spacing between them ranging from 0.6 to 0.8 μm.

[0038] Immersion EIS results are shown in Figure 4 . The EIS impedance of the coating of Comparative Example 1, the coating of Comparative Example 2 and the coating of Example 1 all showed a downward trend. At the beginning of immersion, the coating of Comparative Example 1 had a large decline, while the declines of the coatings of Comparative Example 2 and Example 1 were both lower, and the coating impedance of Example 1 was the highest. After the immersion time reached 168h, the impedance value of the coating of Comparative Example 1 had dropped significantly, while the declines of the coatings of Comparative Example 2 and Example 1 were still lower than that of the coating of Comparative Example 1. The water-based fluorocarbon coating resistance of Example 1 was the largest throughout the immersion test. This shows that during the 168h immersion cycle in the corrosive medium, the DL-Al 2 O 3 In water-based fluorocarbon coatings, doping is relatively 2 O 3 The doping of has a better resistance to the corrosive medium. Examples 2-5 are all better than Comparative Examples 1 and 2 to varying degrees.

[0039] Figure 5 The porosity change and its linear fitting curve are calculated during the immersion test. Before immersion, the porosity of the coating of comparative example 2 and the coating of example 1 is lower than that of the coating of comparative example 1. The slope of the fitting curve of the coating of example 1 is the smallest, which is 1.32825×10 -8 , indicating that with the increase of immersion time, the porosity of the water-based fluorocarbon coating doped with the coating in Example 1 increases slower than that of other coatings. Examples 2-5 all show lower porosity, indicating that DL-Al 2 O 3 It can better reduce the coating porosity and the void growth rate when immersed in corrosive media.

[0040] The results of the coating salt spray corrosion test of Comparative Examples 1, 2 and Example 1 are shown in Figure 6. All three coatings showed no obvious corrosion within 12 hours of corrosion. When the corrosion time reached 48 hours, the corrosion of the coating in Comparative Example 1 gradually expanded, and bubbling occurred in the coating, while the corrosion area of ​​the coating in Comparative Example 2 also began to expand, and new corrosion areas appeared. The corrosion area of ​​the coating in Example 1 expanded less, and new corrosion points also appeared, but the coating did not show bubbling. When the corrosion time reached 168 hours, a larger area of ​​corrosion and bubbling occurred in the coating of Comparative Example 1, a larger area of ​​corrosion occurred in the coating of Comparative Example 2, and the coating began to bubble, while the corrosion area of ​​the coating of Example 1 increased but was less than that of other coatings, and the coating did not show bubbling. Examples 2-5 are similar to Example 1, all showing lower corrosion areas and growth rates.

Claims

1. A method for preparing a water-based fluorocarbon coating having a micro-nanoscale wrinkle structure, the specific steps of which are as follows: (1) using anhydrous ethanol as a solvent and isopropyl distearoyloxyaluminate as a solute to prepare a modifier with a mass concentration of 1 to 3%, adding 5 to 6% of the mass of the modifier to the solution system to form a suspension, stirring, reacting for 240 to 270 minutes, and centrifugally washing and drying after stirring to obtain modified nano alumina; (2) Using the modified nano-alumina as a filler, adding an aqueous fluorocarbon resin, a wetting agent, an emulsifier and a defoaming agent, stirring, and ultrasonically dispersing to obtain an aqueous fluorocarbon emulsion; coating the emulsion on a substrate, drying in an oven and curing to form a coating.

2. The preparation method according to claim 1, characterized in that The components and their weight parts in the water-based fluorocarbon emulsion are: 40-50 parts of water-based fluorocarbon resin, 1 part of filler, 0.5-2 parts of wetting agent, 1-2 parts of emulsifier, and 1-2 parts of defoaming agent.

3. The preparation method according to claim 1, characterized in that The wetting agent is polyoxyethylene alkylphenyl ether or polyoxyethylene fatty acid ester; the emulsifier is OP-10, polysorbate TW-85 or sodium dodecylbenzene sulfonate (SDBS); and the defoaming agent is 1-octanol, liquid paraffin or silicone.

4. The preparation method according to claim 1, characterized in that The thickness of the latex coated on the substrate is 150um±10um; the thickness of the coating after drying and curing is 60±5um.

5. The preparation method according to claim 1, characterized in that The substrate is carbon steel.

Citation Information

Patent Citations

  • Graphene-modified high-TG2 heavy anti-corrosion powder coating and preparation method thereof

    CN111410911A

  • Bionic structure strain insensitive conductive fiber and preparation method thereof

    CN113062116A

  • Aerogel heat-insulation and heat-preservation nano coating

    CN115011153A

  • Warm-mix smoke suppression modified asphalt and preparation method thereof

    CN117264431A

  • High-weather-resistance FEVE water-based two-component fluorocarbon coating and production process

    CN117363184A